Simulated Microgravity Culture System for a 3-D Carcinoma Tissue Model. (November 2002) - Nakamura, K.; Kuga, H.; Morisaki, T.; Baba, E.; Sato, N.; Mizumoto, K.; Sueishi, K.; Tanaka, M.; Katano, M.
An in vitro organotypic culture model is needed to understand the complexities of carcinoma tissue consisting of carcinoma cells, stromal cells, and extracellular matrices. We developed a new in vitro model of carcinoma tissue using a rotary cell culture system with four disposable vessels (RCCS TM -4D) that provides a simulated microgravity condition. Solid collagen gels containing human pancreatic carcinoma NOR-P1 cells and fibroblasts or minced human pancreatic carcinoma tissue were cultured under a simulated microgravity condition or a static 1g condition for seven days. NOR-P1 cultures subjected to the simulated microgravity condition showed greater numbers of mitotic, cycling (Ki-67-positive), nuclear factor-κ B-activating cells, and a lower number of apoptotic cells than were shown by cultures subjected to the static 1g condition. In addition, human pancreatic carcinoma specimens cultured under the simulated microgravity condition maintained the heterogeneous composition and cellular activity (determined by the cycling cell ratio and mitotic index) of the original carcinoma tissue better than static culture conditions. This new 3-D rotary cell culture system with four disposal vessels may be useful for in vitro studies of complex pancreatic carcinoma tissue.